The guide to investigation of mouse pregnancy - Adamson, S. Lee 1954-; Croy, B. A. (B. Anne); DeMayo, Francesco J.; Yamada, Aureo T. (Elsevier/AP, 2014)
The Guide to Investigation of Mouse Pregnancy is the first publication to cover the mouse placenta or the angiogenic tree the mother develops to support the placenta. This much-needed resource covers monitoring of the cardiovascular system, gestational programming of chronic adult disease, epigenetic regulation, gene imprinting, and stem cells. Offering detailed and integrated information on how drugs, biologics, stress, and manipulations impact pregnancy in the mouse model, this reference highlights techniques used to analyze mouse pregnancy.